Factor affecting foreign labor productivity in oil palm plantation / Nurhazira Mohd Hasni and Nur Aziera Ruslan - Mohd Hasni, Nurhazira; Ruslan, Nur Aziera (Faculty of Plantation and Agrotechnology, 2018)
Oil palm plantation is rapidly grown nowadays. Due to the growing of plantation sector, labor shortage is occurred. There are several factors need to study and investigate due to this issue. This study was carried out to examine factors affecting foreign labor productivity in oil palm plantation. The study was conducted at FELCRA Berhad, Kluang among 71 respondents which are randomly selected in FELCRA Berhad Sungai Sepuluh and FELCRA Berhad Simpang Renggam. After survey process the data collected will be analyzed by using Statistical Package for Social Science (SPSS) version 22.0 to obtain reliability test, descriptive analysis, correlation coefficient and multiple regressions that related to variable of wages, welfare management, training and attitude in this study. From correlation analysis, the result indicates that there is a positive linear relationship between wages, training and attitude that affected foreign labor productivity in this study. It was indicated as moderate correlation where the wages (p=0.299), training (p=0.393) and attitude (p=0.371). Through the regression analysis, 26.6% factors affected foreign labor productivity was explained by independent variables which are wages, training and attitude. The others 73.4% were explained by the other factor. Training was identified as the most dominant factor that affect foreign labor productivity in oil plantation (β=0.388). Therefore, training plays a vital role to the workers especially to unskilled worker and to the worker with lack of experiences. Hence, the company needs to improves training among workers to gain more knowledge and increase their performance as well as their skills and capabilities.